2016
DOI: 10.3897/zookeys.574.8037
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterisation, and phylogenetic position of X. browni sp. n., X. penevi sp. n. and two known species of Xiphinema americanum-group (Nematoda, Longidoridae)

Abstract: Using ribosomal (18S, ITS1, ITS2, D2-D3 expansion segments of 28S rDNA) and mitochondrial (partial cox1 and nad4) DNA markers in a study of several populations of Xiphinema americanum-group from Europe and Morocco, two cryptic species Xiphinema browni sp. n. (formerly reported as Xiphinema pachtaicum) and Xiphinema penevi sp. n. were revealed. The species are described, illustrated and their phylogenetic relationships discussed. The first species is most similar to Xiphinema parasimile and is a member of Xiphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…pachtaicum sequenced during the present study (MF372940), revealed it has 99% identity with other sequences of the species (KU250139, KP407873, AM086682, MH484520) and an isolate of X . penevi Lazarova, Peneva & Kumari, 2016 [16] (KU250141) available in GenBank. No phylogenetic analyses were performed in the present study using this sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pachtaicum sequenced during the present study (MF372940), revealed it has 99% identity with other sequences of the species (KU250139, KP407873, AM086682, MH484520) and an isolate of X . penevi Lazarova, Peneva & Kumari, 2016 [16] (KU250141) available in GenBank. No phylogenetic analyses were performed in the present study using this sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term association of the nematode with its endosymbiont and species-specific associations are already hypothesized [34]. Recent studies have emphasized identification [16] and cophylogenetic analyses of these endosymbiont bacteria with their host nematodes [10, 34], to corroborate the long-term association and significant cophylogeny between nematode host and endosymbiont. In one of the aforementioned studies [34], a new endosymbiont, belonging to the plant and fungal endosymbionts of the family Burkholderiaceae Garrity, Bell & Lilburn, 2005 [35] was discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The Bayesian Inference (BI) algorithm implemented in MrBayes 3.2.5 was used for phylogenetic relationships reconstructions (Huelsenbeck and Ronquist 2001; Ronquist et al 2012). For further details, see Lazarova et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The protein coding mitochondrial gene, cytochrome oxidase subunit I ( coxI ), has been described as a reliable and preferred molecular barcode and a useful tool for highlighting the intra-specie variation within some species of X. americanum -group (Lazarova et al 2006; Gutiérrez-Gutiérrez et al 2012; Lazarova et al 2016; Orlando et al 2016; Palomares-Rius et al 2017). In the present study, coxI gene was used to reconstruct the phylogenetic relationship within the species; thus, in combination with morphological identification, it provided a useful tool for delimitation and discrimination of X. oxycaudatum from other species within the americanum -group.…”
Section: Discussionmentioning
confidence: 99%